Inventarisasi Kupu-Kupu (Lepidoptera: Rhopalocera) di Dua Kawasan Air Terjun Kota Padang, Sumatera Barat (Universitas PGRI Sumatera Barat, 2019)
This study aims to identify of butterflies found in two waterfall areas in the city of Padang. Sampling was carried out in March - April 2018 with the transect walk method,Â butterflies were captured using insect net. Total butterflies obtained were 179 individuals consisting of 51 species belonging to 37 genera and 7 families. The highest number of species found in the family Nymphalidae (17 species), followed by Papilionidae (10 species), Lycaenidae (6 species), Pieridae (6 species), Satyridae (6 species), Danaidae (4 species), and Amathusidae (2 species ) The most common species is Junonia atlites (Linnaeus).Â